Regulação do mercado de infraestrutura: o equilíbrio econômico-financeiro e seus reflexos sobre a política e a economia - Glassman, Guillermo Santana Andrade (2016)
The present research, in an interdisciplinary approach, relates legal aspects involved in economic and financial balance on public infrastructure contracts to its reflex in Brazilian economy and politics. Besides legal dispositions on the matter, the analysis also covers parameters that are usually adopted by the legal doctrine to delineate the contractual equation in these circumstances. A simplified interpretation of the concept, viewed generically as a relation between charges incurred in the contract and retributions by the public contractor has imposing consequences to achieve rebalancing. In this sense, we have found that the wide discretion used to evaluate rebalancing contractual claims has significantly contributed to abandonment of infrastructure enterprises and adoption of illegal rebalancing solutions, which is a structural problem in this market. Proposing a new approach to the concept, in which risk and contingency have a crucial importance to complex contracts, this work delineates possible objective elements to appreciate public infrastructure contracts. This proposed process begins with prior assessment and provision, in the legal sphere, of the risks commonly related to this type of enterprise. Secondly, a proper contract modeling will bring specific allocation of risks regime for this type work. Finally, project contract management monitoring activity will enable a definitive delimitation of the scheme and will form the material ballast evidentiary that will allow an objective assessment of the relevance and size of contractual rebalancing. We sustain the hypothesis that this approach would have a deterrent effect on the abandonment of infrastructure projects by contractors for their implementation and on corrupt practices taking place in the contractual rebalancing process.